Patient Perspectives on the Burden and Prevention of Diabetes-Related Foot Disease. Issue 3 (June 2023) - Crowley, Benjamin; Drovandi, Aaron; Seng, Leonard; Fernando, Malindu E.; Ross, Diane; Golledge, Jonathan
Purpose: The purpose of the study was to understand patient perspectives about the impact and prevention of diabetes-related foot disease (DFD). Methods: An online survey was distributed to patients with a history of DFD during 2020. The survey was designed alongside clinical specialists and DFD patients and utilized the health belief model. It asked about the impact of DFD on health, perceptions on preventive strategies, perceived need for additional support, and patient preferences for telehealth in DFD management. Quantitative data were summarized descriptively and compared between groups. Open-text responses were analyzed using conceptual content analysis. Results: Of 80 participants with a history of DFD, foot ulcers were the complication most often experienced, with over two-thirds having been admitted to hospital for a DFD-related issue and over one-third having a DFD-related amputation. Participants had ranging perceptions on the effect of DFD on health, from minimal to crippling. Those with previous severe DFD complications leading to hospital admission found a lack of mobility and independence the consequences of most concern. Using offloading footwear was perceived as very important for preventing DFD complications, although the use of offloading footwear was low, with participants citing issues relating to cost, comfort, appearance, and access to footwear as barriers to better adherence. Perceptions on telehealth were mixed, with many participants not having access to or being comfortable with the use of digital technologies. Conclusions: Patients with DFD require additional supports for effective prevention, including offloading footwear.